Educational Innovation For The Future Generation - Tiansi Bronson; Nepri Putri Jolanda; Sri Wahyuni (JEIT (Journal of Educational Innovations and Technologies), 2025)
In an era characterized by rapid technological change and global uncerainty, educational innovation is vital for preparing future generations to thrive. This study investigates four interrelated pillars of educational transformation: the integration of technology, active and collaborative pedagogy, the development of soft skills, and the analysis of systematic challenges. Drawing from authoritative sources such as UNESCO, OECD, and the World Economic Forum, this research emohasizes that innovation goes beyond adopting tools-it requires rethingking educational aims, structures, and delivery. The methodology includes literature analysis and conceptual synthesis, focusing on both internal (leadership, curriculum, school culture) and external (policy, social support, global challenges) factors that influence innovation. The findings highlight the need for inclusie, equity-driven reforms supported by proffesional development, flexible curricula, and community engagement. The study concludes that authentic innovation fosters ethical, resilient, and adaptable learnes. Therefore, a holistic approach-combining technological advancement with pedagogical and systemic change-is essential to ensure education remains relevant and transformative. The insights provided serve as a framework for policymarkers, educators, and institutions aiming to design sustainable educational systems for the future.